FAKTOR-FAKTOR PENUNJANG DAN PENGHAMBAT DALAM PELAKSANAAN PEMBELAJARAN DARING (ONLINE) PPG DALAM JABATAN (DALJAB) PADA GURU PEREMPUAN DI ACEH - Lailatussaadah, Lailatussaadah; Fitriyawany, Fitriyawany; Erfiati, Erfiati; Mutia, Sri (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2020)
The low quality of education in Indonesia has something to do with the low quality of teacher. Meanwhile, facing the challenge of 4.0 era, teacher is supposed to prepare the student to have the competencies and master the information and technology. Thus, professional teacher is absolutely needed in order to increase the quality of education. To solve this problem, the government conduct the Teacher Professionalism Improvement Program (PPG). This study is aimed at investigating the pros and cons in applying the online PPG daljab for Female teachers in Aceh province. This study is conducted through the qualitative approach, interview, observation and documentation. The subjects of this study are consisting of four female teachers, three online facilitators. Whilst, the data analysis techniques were conducted through the Miles and Hubberman models. The result of this study shows that there are two supporting factors in the success of the implementation of online PPG for the female Acehnese teachers. First, the support is from the online group members and then the second is from the support from the family members in operating the Information and Technology (IT) related issues. Meanwhile, the cons factors are the disability of the teacher to operate the laptop, poor internet connection, lack of focuses due to the teaching tasks at school, and the teacher motivation in mastering the IT and applying it in the teaching learning process. Therefore, it can be concluded that the program evaluation and IT training for in- service PPG are absolutely required. It is essential to conduct an IT empowerment for the pre- training teacher in the basis of the network availability and age.